Nutrient use efficiency indices as influenced by nutrient management practices under cotton-green gram intercropping system in vertisols - Pratik Ramteke; Vijay Gabhane (Environment Conservation Journal, 2023)
A field study was conducted during 2021-22 at the Research field of All India Coordinated Research Project for Dryland Agriculture (AICRPDA), Dr. Panjabrao Deshmukh Krishi Vidyapeeth, (Dr. PDKV) Akola, Maharashtra (India), on an ongoing long-term experiment initiated in 1987-88 under cotton + green gram (1:1) intercropping system in Vertisols. The eight treatments comprised of a control, sole use of organics and chemical fertilizers, and integration of organics with chemical fertilizers to partially substitute Nitrogen (N). The results after 35th cycle revealed that the uptake of N, Phosphorus (P), and Potassium (K) was significantly higher in Integrated Nutrient Management (INM) treatments, particularly the treatments T6 and T7 where 50 percent N was substituted by either gliricidia or Farm Yard Manure (FYM). Further, the various parameters of nutrient use efficiency of N, P, and K were also found to be significantly higher in INM treatments followed by T2 (100% RDF). Therefore, the present investigation concludes that under the cotton + green gram intercropping system in Vertisols, INM that involves conjoint use of different nutrient sources appears to be a promising strategy for improvement in fertilizer use efficiency as a whole including Nutrient Use Efficiency (NUE).